A Comparative Study on Ratings of Indian Wine with Imported Wine - Dr. Abhishek Kumar (International Journal of Engineering and Management Research, 2021)
The study attempts to determine the gaps of wine consumers ratings to Indian wine as compare with imported wine. Twelve parameters are used to compare the ratings of Indian with Imported wine on five-point scale. 325 wine consumers have selected for this study from major wine consuming regions of India. Correlation Coefficient and student t test were used to examine wine consumers ratings. The study found that there is highly significant difference in the ratings given to Indian and Imported wine. This paper reveals that wine consumers consider imported wine superior to Indian wine.